Guide to Participatory Scenario Planning (PSP): Experiences from the Agro-Climate Information Services for women and ethnic minority farmers in South-East Asia (ACIS) project in Ha Tinh and Dien Bien province, Vietnam - Le Thi Tam; Luu, Thi Thu Giang; Simelton, Elisabeth; Carter, Anoushka; Le, Dinh Hoa; Tong, Thi Huong (2018)
The Participatory scenario planning (PSP) workshop is a valuable knowledge-sharing platform through which stakeholders, including those who support the implementation of PSP (i.e., meteorological and agricultural services) and those who access and use the climate information (i.e., technical experts, and farmers) meet to discuss adaptation actions within the context of climate information. The PSP approach was developed under CARE International’s Adaptation Learning Programme (ALP). It was then adapted to Vietnam, Laos, and Cambodia under the Agro-Climate Information Services for women and ethnic minority farmers in South-East Asia (ACIS) project by CARE International in Vietnam and World Agroforestry Centre (ICRAF) Vietnam.